Long survival in a child with a mutated K27M‐H3.3 pilocytic astrocytoma. (3rd March 2015) - Hochart, Audrey; Escande, Fabienne; Rocourt, Nathalie; Grill, Jacques; Koubi‐Pick, Valérie; Beaujot, Juliette; Meignan, Samuel; Vinchon, Matthieu; Maurage, Claude Alain; Leblond, Pierre
Abstract We report the first case of a child with a H3F3A K27M mutated pilocytic astrocytoma, who presented with a 10 years survival, and underwent spontaneous malignant transformation. The complex tumoral chromosomal rearrangements were consistent for genomic instability and for the histopathological features of malignant transformation into glioblastoma. H3F3A K27M mutations are rarely observed in benign neoplasms and may be associated with an adverse outcome. This mutation might not be the major driver that led to the onset of tumorigenesis, and we could consider that the associated TP53 mutation, would be required for malignant transformation.